Literasi Keuangan Islam di Perdidikan Tinggi Islam: Kajian Empiris di UIN Alauddin Makassar - Salmah Said; Andi Muhammad Ali Amiruddin (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
Literacy is related to one’s competence or knowledge of particular or specific disciplines/areas. Financial literacy is one's knowledge of finance and his ability to make effective financial decisions. Thus, Islamic financial literacy represents one’s level of knowledge about Islamic financial comprehensively. The aim of this study is to examine the level of Islamic financial literacy of civitas academica (lecturers, students, and employees) of State Islamic University (UIN) of Alauddin Makassar. The study reveals that, in general, the Islamic financial literacy of civitas academica of UIN Alauddin Makassar is still low. Furthermore, financial literacy on Islamic banking is still dominated compare to other Islamic financial institutions. Finally, this study also shows that financial literacy level of female respondents is higher than their male counterparts.